Development of seaweed cultivation in Latin America: current trends and future prospects. Issue 5 (3rd September 2019) - Alemañ, Alejandro Espi; Robledo, Daniel; Hayashi, Leila
ABSTRACT: Seaweed farming has now expanded across several continents from South East Asia to South America, Northern Europe, Canada and East Africa, contributing to global food security, supporting rural livelihoods, alleviating poverty and improving the health of oceans. Latin America (LA) covers a vast geographical area, which includes four different oceanic domains (Temperate Northern Pacific, Tropical Eastern Pacific, Temperate South America and Tropical Atlantic) and encompasses many types of coastal ecosystems with a wide range of seaweed species. LA has major potential for the development of seaweed farming activities; however, almost all the production is based on the harvesting of natural beds. This review describes the development of and prospects for the aquaculture seaweed industry in LA. The status of the seaweed aquaculture sector for green, brown and red seaweed and the main industry challenges are addressed. Regulation in the primary countries is also discussed. The expansion of the aquaculture industry in this region can be improved with new strains and farming methodologies, diversification of species, market expansion and an increase in domestic demand.